Three-Dimensional Migration of Human Amniotic Fluid Stem Cells Involves Mesenchymal and Amoeboid Modes and is Regulated by mTORC1. (4th August 2021) - Rosner, Margit; Hengstschläger, Markus
Abstract: Three-dimensional (3D) cell migration is an integral part of many physiologic processes. Although being well studied in the context of adult tissue homeostasis and cancer development, remarkably little is known about the invasive behavior of human stem cells. Using two different kinds of invasion assays, this study aimed at investigating and characterizing the 3D migratory capacity of human amniotic fluid stem cells (hAFSCs), a well-established fetal stem cell type. Eight hAFSC lines were found to harbor pronounced potential to penetrate basement membrane (BM)-like matrices. Morphological examination and inhibitor approaches revealed that 3D migration of hAFSCs involves both the matrix metalloprotease-dependent mesenchymal, elongated mode and the Rho-associated protein kinase-dependent amoeboid, round mode. Moreover, hAFSCs could be shown to harbor transendothelial migration capacity and to exhibit a motility-associated marker expression pattern. Finally, the potential to cross extracellular matrix was found to be induced by mTORC1-activating growth factors and reduced by blocking mTORC1 activity. Taken together, this report provides the first demonstration that human stem cells exhibit mTORC1-dependent invasive capacity and can concurrently make use of mesenchymal and amoeboid 3D cell migration modes, which represents an important step toward the full biological characterization of fetal human stem cells with relevance to both developmental research and stem cell-based therapy. : This study on human amniotic fluid stem cells (hAFSCs) provides the first demonstration that human stem cells exhibit mTORC1-dependent invasive capacity and can concurrently make use of mesenchymal and amoeboid 3D cell migration modes. These results represent an important step toward the full biological characterization of fetal human stem cells with relevance to developmental research and stem cell-based therapy.